Vision-Related Quality of Life in Primary Angle-Closure Glaucoma Patients with or without Visual Field Dysfunction. (20th March 2023) - Ma, Pingping; Liu, Yingru; Su, Yufang; Yang, Yajun
Abstract : Purpose . To evaluate the association between visual-related quality of life (VRQoL) and visual field (VF) loss in patients with primary angle-closure glaucoma (PACG). Methods. In this case-control study, a total of 79 patients with PACG (with or without VF detects) and 35 healthy controls were included. The patients underwent the 25-item National Eye Institute Visual Functioning Questionnaire (NEI VFQ-25), clinical examination, and VF testing. VF defects were identified by simplified Hodapp's classification. NEI VFQ-25 scores were compared between the three groups. Results. No significant differences were found in gender, VFQ rating for "composite score" and "color vision" between the three groups. PACG patients with VF loss were most likely to be older and had lower best corrected visual acuity (BCVA), spherical equivalent (SE), mean deviation (MD), and visual field index (VFI), but higher pattern standard deviation (PSD) (all P < 0.05 ). Furthermore, patients with VF loss had significantly lower NVE-VFQ-25 subscale scores for general health, general vision, ocular pain, near activities, distance activities, social functioning, mental health, role difficulties, dependency, driving, and peripheral vision than PACG patients without VF loss and healthy controls (all P < 0.05 ). VFI ( β  = 1.498, P = 0.003 ) and MD ( β  = −3.891, P = 0.016 ) were significantly correlated with Role Difficulties scores. Additionally, PSD was significantly correlated with Peripheral Vision scores ( β  = −1.346, P = 0.003 ). Conclusions. PACG patients with VF loss reported lower NEI VFQ-25 composite and subscale scores. VF indices including VFI, MD, and PSD were strongly correlated with VRQoL as assessed by NEI VFQ-25; thus, VRQoL may be significantly impacted by glaucomatous VF defects.